Dramen der Schwangerschaft Friedrich Hebbels ,Judith', ,Maria Magdalena' und ,Genoveva' - Villinger, Antonia (Literatura, 2021)
In his plays 'Judith', 'Maria Magdalena' and 'Genoveva' Friedrich Hebbel tells different stories about pregnancy. Working with theories from gender, queer, and embodiment studies the book focuses on textual constellations, in which the literary figures start to imagine the unborn in the female womb, think about the social consequences of an (illegitimate) pregnancy and reflect on birth and procreation as well as on concepts of body and gender. By combining research from literary studies with perspectives of the history of knowledge, the study further offers an innovative perspective on the presentation of pregnancy in dramatic plays of the 19th century.